Laboratory evaluation of two point-of-care detection systems for early and accurate detection of influenza viruses in the Lao People's Democratic Republic. (March 2021) - Kittikraisak, Wanitchaya; Khamphaphongphane, Bouaphanh; Xayadeth, Sinakhone; Som Oulay, Virasack; Khanthamaly, Viengphone; Sengvilaipaseuth, Onanong; Davis, C. Todd; Yang, Genyan; Zanders, Natosha; Mott, Joshua A.; Xangsayarath, Phonepadith
Highlights: Recent pandemics highlight the threat that novel influenza viruses present to humans. It is critical to improve the quality and timeliness of surveillance systems. Early detection of novel influenza viruses is essential to containing an emerging pandemic. We describe the performance of molecular-based point-of-care detection systems for influenza virus detection. These systems could improve outbreak response and clinical decision-making. Abstract: Background: We evaluated molecular-based point-of-care influenza virus detection systems in a laboratory prior to a field evaluation of on-site specimen testing. Methods: The performance characteristics of 1) insulated isothermal polymerase chain reaction (PCR) on a POCKIT™ device and 2) real-time reverse transcription-PCR (rRT-PCR) on a MyGo Mini™ device were evaluated using human clinical specimens, beta-propiolactone-inactivated influenza viruses, and RNA controls. The rRT-PCR carried out on a CXF-96™ real-time detection system was used as a gold standard for comparison. Results: Both systems demonstrated 100% sensitivity and specificity and test results were in 100% agreement with the gold standard. POCKIT™ only correctly identified influenza A (M gene) in clinical specimens due to the unavailability of typing and subtyping reagents for human influenza viruses, while MyGo Mini™ had either a one log higher or the same sensitivity in detecting influenza viruses in clinical specimens compared to the gold standard. For inactivated viruses and/or viral RNA, the analytic sensitivity of POCKIT™ was shown to be comparable to, or more sensitive, than the gold standard. The analytic sensitivity of MyGo Mini™ had mixed results depending on the types and subtypes of influenza viruses. Conclusions: The performance of the two systems in a laboratory is promising and supports further evaluation in field settings.